Pengaruh Kemudahan Penggunaan dan Kepercayaan Terhadap Minat Menggunakan Layanan M2U pada Generasi Z di Bandar Lampung - Edward Edward; Yusuf Sulfrano Barusman; Haninun Haninun (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The development of digital banking in Indonesia has shown significant growth; however, the adoption rate of Maybank Indonesia’s M2U service among Generation Z in Bandar Lampung remains suboptimal. This study aims to analyze the effect of perceived ease of use and trust on the intention to use the M2U service among Generation Z in Bandar Lampung. The research employed a quantitative approach with a causal associative design. The population consisted of 4,600 Generation Z users of the M2U application at KCI Bandar Lampung, with a sample of 98 respondents determined using the Slovin formula. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that perceived ease of use has a positive and significant effect on the intention to use the M2U service. Trust also has a positive and significant effect on the intention to use the service. Simultaneously, perceived ease of use and trust significantly influence Generation Z’s intention to use M2U in Bandar Lampung. The study concludes that improving application usability and strengthening security and user trust are key factors in increasing Generation Z’s intention to adopt M2U digital banking services.